Enhanced coupling of broadband light into amorphous silicon via periodic nanoplasmonic arrays *DISTRIBUTION STATEMENT A. Approved for public release: distribution unlimited. This material is based upon work supported by the Department of the Army under Air Force Contract No. FA8721-05-C-0002 and/or FA8702-15-D-0001. Any opinions, findings, conclusions or recommendations expressed in this material are those of the author(s) and do not necessarily reflect the views of the Department of the Army. (17th July 2018) - Liberman, V; Parameswaran, L; Rothschild, M; Ait-El-Aoud, Y; Luce, A; Okamoto, M; Willcox, W B; Giardini, S; Osgood, R M
Abstract: Achieving enhanced coupling of solar radiation over the full range of the silicon absorption spectrum up to the bandgap is essential for increased efficiency of solar cells, especially thin film versions. While many designs for enhancing trapping of radiation have been explored, detailed measurements of light scattering inside silicon cells is still lacking. Here, we demonstrate experimentally and computationally that plasmonic-assisted localized and traveling modes can efficiently couple red and infrared radiation into ultrathin amorphous silicon (a-Si) layers. Utilizing patterned periodic arrays of aluminum nanostructures on thin a-Si, we perform specular and diffuse reflectivity and transmission measurements over a broad spectrum. Based on these results, we are able to separate parasitic absorption in aluminum plasmonic arrays from enhanced light absorption in the 200 nm thick amorphous silicon layer, as compared to a blank silicon layer. We discover a very efficient near-infrared a-Si absorption mechanism that occurs at the transition from the radiative to evanescent diffractive coupling, analogous to earlier surface-enhanced infrared studies. These results represent a direct demonstration of enhanced radiation coupling into silicon due to large angle scattering and show a path forward to improved ultrathin solar cell efficiency.